Antibacterial Activity of Imported Honey against Methicillin Resistant Staphylococcus aureus (MRSA) Isolated from Infected Wounds - Khadija Muhammad Lawan; Binta Muhammad Aminu; Abdulrazak Muhammad Hussain; Abdulmumin Yunusa (UMYU Journal of Microbiology Research)
The use of traditional and herbal medicine to treat infections has been in practice since the origin of mankind, and it was the only option for treatment before the era of antibiotics. This research work was aimed at evaluating the antibacterial activity of imported honey against methicillin resistant Staphylococcus aureus isolated from different wound infections.152Samples from different wounds were obtained from patients with infected wounds attending Murtala Muhammad Specialist Hospital and Muhammadu Abdullahi Wase Specialist Hospital, Kano. The isolates were identified and confirmed using biochemical tests. The antibacterial activity of the honey and minimum inhibitory concentration (MIC) against the isolates were determined using agar well diffusion and two-fold dilution method respectively. The results to detect MRSA revealed its incidence as 24.9%. The result of the antibacterial activity of honey revealed activity at all the concentrations with the diameter of zones of inhibition ranging from 8-34mm.The two imported honey used in the study showed varied bacteriostatic activities, and none of the isolates was resistant to the tested honeys. Therefore, the antibacterial activity of honey even at lower strength justify their efficacy in the treatment of wound infection.